Pendampingan Implementasi Deep Learning dalam Layanan Bimbingan Konseling di SMA Kabupaten Demak - Ismah; Lestari, Farikha Wahyu; Kurniawan, Latif Anshori (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
A deep learning understanding is essential for Guidance and Counseling (Bimbingan Konseling, BK) teachers to support their duties in optimally supporting student development. Adapting deep learning in providing BK services is expected to make BK services more meaningful, enjoyable, and support student engagement. The complexity of problems faced by students requires BK teachers to update their knowledge and skills. Through this partnership program, BK teachers will gain a new understanding related to deep learning and its application in BK. This activity consists of several stages, namely: activity socialization, implementation stage, independent projects, and evaluation and follow-up activities. This Community Service (Pengabdian kepada Masyarakat, PkM) activity/program aims to improve the understanding and ability of BK teachers in implementing a deep learning approach in BK services, especially for members of the Guidance and Counseling Teachers’ Council (Musyawarah Guru BK, MGBK) at the senior high school level in Demak Regency. This training covers three main topics: the characteristics of Generation Z and their learning styles, the concept of deep learning in learning, and the implementation of deep learning in BK services. The activity method included material delivery, discussion, and evaluation through pre- and post-tests. The evaluation results showed a significant increase in the average score for general understanding and the application of deep learning. Participants also expressed high enthusiasm for this approach and hoped for further training. The activity concluded that the deep learning approach is highly relevant for implementation in guidance and counseling services, addressing the reflective and collaborative thinking needs of Generation Z students.